The Role of AI in Administrative Decision-Making : A Study of the Opinions of a Sample of Academics in Iraqi Universities - Majeed, Ahmed W. (PROSPECTIVE RESEARCHES, 2025)
The research aims to shed light on artificial intelligence (AI) technology and its application in administrative tasks, particularly in decision-making. To achieve this, a questionnaire was designed consisting of 30 questions addressing the most common and influential aspects of AI on administrative decisions, using a five-point Likert scale. The study revealed a significant correlation between AI and administrative decision-making. Additionally, it found that this relationship varies depending on the decisions of each administrative department. This indicates that AI contributes to enhancing the efficiency of decision-making and assists managers in improving their decisions.